Endoplasmic Reticulum Stress Mediates Renal Tubular Vacuolation in BK Polyomavirus-Associated Nephropathy - Zhao, Guo-Dong; Gao, Rong; Hou, Xiao-Tao; Zhang, Hui; Chen, Xu-Tao; Luo, Jin-Quan; Yang, Hui-Fei; Chen, Tong; Shen, Xue; Yang, Shi-Cong; Wu, Cheng-Lin; Huang, Gang (Frontiers in Endocrinology, 2022)
Objective This study aimed to explore the molecular mechanism of cytoplasmic vacuolation caused by BK polyomavirus (BKPyV) and thus search for potential target for drug repurposing. Methods Morphological features of BK polyomavirus-associated nephropathy (BKPyVAN) were studied under light and electron microscopes. Microarray datasets GSE75693, GSE47199, and GSE72925 were integrated by ComBat, and differentially expressed genes (DEGs) were analyzed using limma. Furthermore, the endoplasmic reticulum (ER)-related genes obtained from GenCLiP 2.0 were intersected with DEGs. GO and KEGG enrichment pathways were performed with intersection genes by R package clusterProfiler. The single-cell RNA sequencing (scRNA-seq) from a BKPyVAN recipient was analyzed with a dataset (GSE140989) downloaded from Gene Expression Omnibus (GEO) as control for gene set variation analysis (GSVA). Immunohistochemistry and electron microscopy of kidney sections from drug-induced ERS mouse models were performed to explore the association of ERS and renal tubular vacuolation. Protein–protein interaction (PPI) network of the intersection genes was constructed to identify hub target. AutoDock was used to screen Food and Drug Administration (FDA)-approved drugs that potentially targeted hub gene. Results Light and electron microscopes exhibited obvious intranuclear inclusions, vacuoles, and virus particles in BKPyV-infected renal tubular cells. Transcriptome analysis revealed 629 DEGs between samples of BKPyVAN and stable transplanted kidneys, of which 16 were ER-associated genes. GO analysis with the intersection genes illustrated that ERS-related pathways were significantly involved, and KEGG analysis showed a prominent enrichment of MAPK, Toll-like receptor, and chemokine signaling pathways. GSVA analysis of the proximal tubule revealed similar pathways enrichment. An electron microscope image of the kidney from ERS mouse models showed an obvious renal tubular vacuolation with prominent activation of ERS markers verified by immunohistochemistry. Furthermore, DDIT3 was identified as the hub gene based on PPI analysis, and ZINCOOOOO1531009 (Risedronate) was indicated to be a potential drug for DDIT3. Conclusion ERS was involved in renal tubular cytoplasmic vacuolation in BKPyVAN recipients. Risedronate was screened as a potential drug for BKPyVAN by targeting DDIT3.